Perovskite indoor photovoltaics: opportunity and challenges. Issue 36 (2nd September 2021) - Wang, Kai-Li; Zhou, Yu-Hang; Lou, Yan-Hui; Wang, Zhao-Kui
Abstract : With the rapid development of the Internet of Things (IoTs), photovoltaics (PVs) has a vast market supply gap of billion dollars. Abstract : With the rapid development of the Internet of Things (IoTs), photovoltaics (PVs) has a vast market supply gap of billion dollars. Moreover, it also puts forward new requirements for the development of indoor photovoltaic devices (IPVs). In recent years, PVs represented by organic photovoltaic cells (OPVs), silicon solar cells, dye-sensitized solar cells (DSSCs), etc. considered for use in IoTs mechanisms have also been extensively investigated. However, there are few reports on the indoor applications of perovskite devices, even though it has the advantages of better performance. In fact, perovskite has the advantages of better bandgap adjustability, lower cost, and easier preparation of large-area on flexible substrates, compared with other types of IPVs. This review starts from the development status of IoTs and investigates the cost, technology, and future trends of IPVs. We believe that perovskite photovoltaics is more suitable for indoor applications and review some strategies for fabricating high-performance perovskite indoor photovoltaic devices (IPVs). Finally, we also put forward a perspective for the long-term development of perovskite IPVs.